THE CONCEPT OF DOMICILE IN FILLING GOVERNMENT POSITIONS IN THE REGIONS - Putra, Anggi Fitratama Rianto; Phahlevy, Rifqi Ridlo (Journal of Geography, Regional Planning and Development, 2024)
This article discusses the concept of domicile in filling government positions in the regions and discusses how the public can understand the theories on domicile in filling government positions in the regions and discusses the effectiveness of government performance in the regions on the concept of domicile. The research method used is the Normative Method with a statutory approach (Statue Approach) and conceptual approach, and uses qualitative descriptive analysis to analyze the data. The results of this study indicate that there are several concepts on domicile found in the black law dictionary and there is no specific explanation of the definition of domicile in legislation both at the central and regional levels. As well as the concept of domicile that is relevant for application to the system or requirements for filling government positions in Sidoarjo.